DETERMINASI PEMBERIAN MINYAK TRANS TERHADAP STRES OKSIDATIF PADA TIKUS GALUR WISTAR DENGAN MALONDIALDEHIDA PANKREAS SEBAGAI INDIKATOR - Mawali, Maharja; Santoso, Koekoeh; Kusumorini, Nastiti; Satyaningtijas, Aryani Sismin; Supiyani, Atin (Bioma, 2015)
ABSTRACT Trans fatty acids (TFAs) are the entire unsaturated fatty acids containing one or more double bonds isolated in trans configuration believed as predisposing factor of oxidative stress, excluding conjugated double bond fatty acids. Malondialdehyde (MDA) is a product of lipid peroxidation used as oxidative stress marker. The objective of this study was to see the correlation between TFAs containing-oil (consists of 3-6% TFAs) intake at various administration doses and pancreatic MDA levels in Wistar rats. Twelve rats were grouped according to administration doses (20%, 40%, 60% of given feed total energy and control group). TFAs containing-oil was administered orally once a day for 70 days at given doses by force feeding. Pancreatic MDA were measured using TBARS assay adapted from Singh et al. (2006). Increase of TFAs containing-oil administration dose caused insignificant increase of pancreatic MDA level. Keywords: trans fatty acids, oxidative stress, malondialdehyde, Wistar rats, palm oil